Surface Roughness Characteristics and Their Influence on Wind Erosion and Sand Movement - Jie Zhou; Beibei Han; Haifeng Wang (Atmosphere)
Wind erosion significantly threatens sustainable development in desert regions, causing severe soil degradation. Investigating the influence of roughness elements on wind–sand interactions is vital for devising effective wind erosion control strategies. This study examined the effects of smooth and porous surface roughness elements on wind–sand activity and the wind erosion rate of a sand bed surface. Wind tunnel experiments were conducted with 10% coverage of these elements on the sand bed surface under varying wind speeds. Results showed that porous-surfaced roughness elements were less responsive to wind speed than smooth-surfaced spherical elements, significantly slowing wind erosion and enhancing sand bed stability. The porous-surfaced elements significantly reduced wind erosion rates by 21.8% at low wind speeds (8 m/s) and 18.23% at high wind speeds (14 m/s), compared to smooth-surfaced elements. The porous-surfaced spherical roughness elements effectively reduced the secondary lifting of sand particles by increasing the specific surface area, thereby improving the bed surface’s wind erosion resistance. These findings provide critical insights for optimizing sand control materials and developing more effective wind erosion mitigation strategies, offering a valuable reference for combating desertification.